Cytotoxic and Cell Cycle Arrest of Total Alkaloids Extracted from Chelidonium Majus Against Human Colon Cancer (HCT-116). - Fadhil, Yasir B; Al-Sammarraie, Khuldood W; Mohaimen, Nedhal Abdul (Al-Nahrain Journal of Science, 2018)
Chelidonium majus, commonly known as Greater Celandine is a plant widely distributed in nature the plant been used in various traditional system of medicine to treat various disorders. Antitumor activity of total extracted alkaloid of this plant have been studied, there are few studies that examine the properties of the total extracted alkaloids. Thus the objective of this project is to investigate cytotoxic effects of total alkaloid extracted from C. majus against Human colon cancer cell line. Powdered plant material was extracted with methanol by using Soxhlet installation. The extract subjected for acid-base extraction and purification with chloroform to obtain total alkaloids. Cytotoxicity effect of total alkaloids was estimated using MTT-assay in addition to the determination of apoptosis/necrosis FITC Annexin V /PI assay and Cell Cycle Analysis by Pi Staining. It was found that Chelidonium majus contain high amount of total alkaloids where the yield of total extracted alkaloids was about (2.146 %) of total dried weight. The total extracted alkaloids from C. majus showed high significant cytotoxicity effect on (HCT-116) cell lines which was in a dose dependent way, where the IC50 was (67.43 µg/ml). Annexin V-FITC assay showed that total alkaloids from C. majus is strong inducer of apoptosis in HCT-116 cell line. While, the cell cycle arrest evaluation showed that the extract arrests cell cycle progression by significantly restricting cells in different phases (G1, S, G2/M) in a dose dependent way. It is concluded that the plant contains a large quantity of total alkaloids. The total extracted alkaloids showed cytotoxic activity against colorectal cancer (HCT-116) cell line which was in dose dependent manner indicating that the extract could be used in cancer therapy.